CD19-directed chimeric antigen receptor T cell therapy in Waldenström macroglobulinemia: a preclinical model and initial clinical experience. Issue 2 (16th February 2022) - Palomba, M Lia; Qualls, David; Monette, Sebastien; Sethi, Shenon; Dogan, Ahmet; Roshal, Mikhail; Senechal, Brigitte; Wang, Xiuyan; Rivière, Isabelle; Sadelain, Michel; Brentjens, Renier J; Park, Jae H; et al.
Abstract : Background: Waldenström macroglobulinemia (WM) is an incurable disease and, while treatable, can develop resistance to available therapies and be fatal. Chimeric antigen receptor (CAR) T cell therapy directed against the CD19 antigen has demonstrated efficacy in relapsed or refractory B lymphoid malignancies, and is now approved for B cell acute lymphoblastic leukemia and certain B cell lymphomas. However, CAR T therapy has not been evaluated for use in WM. Methods and results: We performed preclinical studies demonstrating CAR T cell activity against WM cells in vitro, and developed an in vivo murine model of WM which demonstrated prolonged survival with use of CAR T therapy. We then report the first three patients with multiply relapsed and refractory WM treated for their disease with CD19-directed CAR T cells on clinical trials. Treatment was well tolerated, and observed toxicities were consistent with those seen in CAR T treatment for other diseases, and no grade 3 or higher cytokine release syndrome or neurotoxicity events occurred. All three patients attained at least a clinical response to treatment, including one minimal residual disease-negative complete response, though all three eventually developed recurrent disease between 3 and 26 months after initial treatment. Conclusions: This report summarizes preclinical and clinical activity of CD19-directed CAR T therapy in WM, demonstrating early tolerability and efficacy in patients with WM, and representing a possible treatment option in patients with heavily pretreated and relapsed or refractory WM. Larger studies evaluating CAR T therapy in WM are warranted, along with further evaluation into mechanisms of resistance to CAR T therapy.